The Antidepressant Quandary: A Qualitative Investigation into the Opinions of Healthcare Professionals Regarding the Prescription of SSRIs in Paediatric Medicine. - Martin, Emily (2008)
Background: Concern exists that childhood and adolescent major depressive disorder is increasing, along with the quantity of prescribed antidepressants to the same age group. The relationship between antidepressants, particularly selective serotonin reuptake inhibitors, and an increase in suicidal behaviours has received much attention over the past few years. Consequently the use of such medications in paediatrics is of some concern.